Vitamin D and IL-10 Deficiency in Preterm Neonates With Bronchopulmonary Dysplasia - Mao, Xiaonan; Qiu, Jie; Zhao, Li; Xu, Junjie; Yin, Jiao; Yang, Yang; Zhang, Mingshun; Cheng, Rui (Frontiers in Pediatrics, 2018)
Introduction: Vitamin D deficiency and inflammation are involved with bronchopulmonary dysplasia (BPD) in preterm neonates; however, the clinical evidence still remains scarce. We hypothesized that vitamin D and inflammatory cytokines may be risk factors for BPD in infants. Methods: Preterm infants born between 28 and 31 weeks’ gestation were recruited between January 2016 and January 2017. Blood samples were all collected at corresponding time points. Vitamin D was measured using an automatic biochemical analyzer, and inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-10) were measured using ELISA. Results: The baseline characteristics for preterm infants without BPD (non-BPD control, n=20) or with BPD (n=19) were similar. In the blood samples collected 24 hours post birth, vitamin D was significantly reduced in the BPD neonates (non-BPD vs BPD, 28.96 ± 3.404 vs 17.99 ± 2.233 nmol/l, p=0.0134). Inflammatory cytokines TNF-α, IL-1β and IL-6 were comparable in both groups. The anti-inflammatory cytokine IL-10, however, was significantly decreased in 24-hour blood samples from BPD preterm infants (non-BPD vs BPD, 44.61 ± 10.48 vs 11.64 ± 2.351 pg/ml, p=0.0054). In the BPD infants with mild or moderate disease, vitamin D deficiency was quite similar. IL-10 deficiency, however, was more aggravated in the BPD infants with moderate disease. No changes in Vitamin D or cytokines (TNF-α, IL-1β, IL-6, and IL-10) were observed for blood samples collected 2 or 4 weeks after birth. Conclusion: In our pilot study, Vitamin D and IL-10 levels at 24 hours of life were risk factors for the development of BPD in very preterm infants.